Draft Seventh Five Year Plan (1985-90) North Eastern Council - Planning Commission (Planning Commission, 1985)
Lying between 22° N-29° 30' N latitude and 89° 47'E-97°25'E longitude the North Eastern Region comprises the five States of Assam, Manipur, Meghalaya, Tripura & Nagaland and the two Union Territories of Arunachal Pradesh and Mizoram. the Region accounts for 7.7 percent of total land space of India and contains 6.89 percent of total population of the country. The northern side of the NE Region is guarded by hill ranges forming part of the Himalayan mountains. In fact, the area abounds in hills intercepted by valleys and adjoined by the plains.
North Eastern Council